2020
DOI: 10.2478/cjf-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Biological Parameters and Fisheries Indices of Beluga Sturgeon Huso Huso in the Southern Caspian Sea

Abstract: There is a significant lack of data for the biological parameters of beluga or great sturgeon, the largest fish in the Caspian Sea. The age, growth and fisheries indices for the stock status of beluga was investigated in the south Caspian Basin of Iran between 1990 and 2011. Fork lengths ranged between 113-420 cm and weights from 8.0 to 725.0 kg. The growth parameters were L∞ = 440 cm, K = 0.027 year−1, t0 = − 5.8 years. The age at first capture (tc) was 13.1 years. The long-term age composition data showed ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
1
4
4
Order By: Relevance
“…The mean weight of the great sturgeon determined in this study was lower compared to that found in the periods from 1990 to 1994 (Taghavi-Motlagh 2001) and from 1990 to 2011 (Fazli et al 2020), and with larger mature individuals which enter the Volga River (Ruban & Khodorevskaya 2011). In general, it was found that females had a greater fork length and body weight compared to males.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…The mean weight of the great sturgeon determined in this study was lower compared to that found in the periods from 1990 to 1994 (Taghavi-Motlagh 2001) and from 1990 to 2011 (Fazli et al 2020), and with larger mature individuals which enter the Volga River (Ruban & Khodorevskaya 2011). In general, it was found that females had a greater fork length and body weight compared to males.…”
Section: Discussioncontrasting
confidence: 72%
“…Only the oldest fish showed multiple vascular channels and compressed or abnormal bands in the margin of the anterior fin spine, which made fin cross sections. The mean fork length of both sexes revealed a decrease in size compared to data for great sturgeon from 1990(Taghavi-Motlagh 2001 and from 1990-2011 (Fazli et al 2020), and also the mean fork length of both females and males was lower than that reported by Ruban & Khodorevskaya (2011) for great sturgeon from the Volga. These differences may be related to the capture of predominantly mature migrating fish in this area, while the catches in the southern part contained both mature and immature fish (Taghavi-Motlagh 2001;Ghadirnejad et al 2010).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Bycatch of juvenile and young A. persicus sharply increased on the eastern coasts of the Caspian Sea from 2000 to 2004, and was expected to increase into the 2010s with effective regulation in the whole Caspian Sea (Moghim et al (2006). However, stocks of all five species declined sharply and were critically endangered (Fazli et al, 2020(Fazli et al, , 2021Fazli, Kaymaram, & Daryanabard, 2022;Khodorevskaya et al, 2014;Ruban & Khodorevskaya, 2011;Tavakoli et al, 2019). In the present study, a bycatch of juvenile and young sturgeon since 2006 was used to assess the status of these species' populations.…”
mentioning
confidence: 85%